2013
DOI: 10.1088/0031-9155/58/13/4501
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo-based diode design for correction-less small field dosimetry

Abstract: Due to their small collecting volume, diodes are commonly used in small field dosimetry. However, the relative sensitivity of a diode increases with decreasing small field size. Conversely, small air gaps have been shown to cause a significant decrease in the sensitivity of a detector as the field size is decreased. Therefore, this study uses Monte Carlo simulations to look at introducing air upstream to diodes such that they measure with a constant sensitivity across all field sizes in small field dosimetry. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 15 publications
1
52
0
Order By: Relevance
“…The overresponse in small radiation fields of silicon diodes, which incorporate silicon of density 2.3 g/cm 3 and possibly other high‐density material in their sensitive volumes and surroundings, has been well documented 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 38 , 39 , 40 , 41 . Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overresponse in small radiation fields of silicon diodes, which incorporate silicon of density 2.3 g/cm 3 and possibly other high‐density material in their sensitive volumes and surroundings, has been well documented 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 38 , 39 , 40 , 41 . Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Diamond detectors, which have a sensitive volume of density 3.5 g/cm 3 , have been reported to overrespond in small fields 16 , 39 , 41 , 42 . Monte Carlo simulations have shown that the magnitude of overresponse is proportional to the mass density of the material in the volume of interest, with a larger overresponse determined for a voxel of the same size in a radiation beam for diamond than for silicon in a 5 mm field for 15 MV (38) .…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent across collimation systems and applies in both the radial direction (pictured in figure 1) and the transverse direction (not pictured). This range encompasses the result of our previous diode-based examination of the beam produced by this linear accelerator, which identified an optimal FWHM of 0.12 cm [17]. …”
Section: Methodsmentioning
confidence: 73%
“…In practice, shielding can be added to diode detectors to limit the large sensitivity for low-photons. As no simple answers can be given what to use and why, one should be aware of the difficulties around diode use in stereotactic beam measurements [31,34,36,46,52,59,81,99] and one should be careful in using them.…”
Section: Diodes Mosfets and Diamond Detectorsmentioning
confidence: 99%